Frequency of Anemia and Iron Deficiency Anemia in Patients with Helicobacter Pylori Infection: A Cross-Sectional Study - Sultan Ahmed Nohario, Bakhat Ali Siyal, Muhammad Ali Memon, Abdul Razzaque Nohri, Sajan, Qurrat Ul Ain Shahid, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of anemia and iron deficiency anemia in patients with Helicobacter pylori infection. Study design: Cross-sectional study Place and Duration: Department of Medicine, Liaquat University Hospital, Hyderabad from May to November 2019 Methodology: We included a total of 140 patients with anemia, either inpatients or outpatients at Liaquat University Hospital in Hyderabad's department of medicine. We acquired demographic information, such as name, gender, and age. The study involved everyone who meets the inclusion requirement. Anemia's brief history, its duration, the colour of the stools (melena black faeces), and the ferritin level were all noted. The cubital vein of either upper arm was used to collect 10 ml of blood, which was then sent to the lab for analysis of anaemia, ID, and H. Pylori detection. A multiparameter cell counter Sysmex k 1000 hematology analyzer was used to determine the amounts of haemoglobin (Hb) and hematocrit (Hct) in the CBC (Tao electronics, Japan). Serum iron levels were evaluated using a Hitachi 917 biochemistry automated analyzer, and ferritin concentrations were determined using a Cobas e411 hormones auto-analyzer from Roche Diagnostics GmbH in Mannheim, Germany (Roche Diagnostics GmbH, Mannheim, Germany). The researcher himself entered all the data on a proforma that had been previously created. Results: Patients' average ages ranged from 40.44± 14.268 years, and their haemoglobin levels were 8.77 ± 3.14. Patients' serum ferritin levels were 10.5 ±63.21 and their BMI was 24.5 ±3.21 respectively. Of the H. pylori patients, there were 70 (50%) anaemic patients and 70 (50%) with normal Hb levels. In this study, 102 individuals (72.9%) had normal serum profiles while 38 patients (27.1%) had iron deficiency anemia. Conclusion: According to our research, treating H. pylori infection may help IDA patients who are infected with the parasite especially those who have moderate to severe anaemia. Individuals with H. pylori infection had a significant prevalence of anaemia and IDA, and both conditions were linked to patients' ages and several behavioural traits Keywords: H. pylori infection, anemia, iron deficiency anemia